A strategy to accelerate protein production from a pool of clones in Chinese hamster ovary cells for toxicology studies. (26th April 2017) - Hu, Zhilan; Hsu, Wendy; Pynn, Abby; Ng, Domingos; Quicho, Donna; Adem, Yilma; Kwong, Zephie; Mauger, Brad; Joly, John; Snedecor, Bradley; Laird, Michael W.; Andersen, Dana C.; et al.
Abstract : In the biopharmaceutical industry, a clonally derived cell line is typically used to generate material for investigational new drug (IND)‐enabling toxicology studies. The same cell line is then used to generate material for clinical studies. If a pool of clones can be used to produce material for IND‐enabling toxicology studies (Pool for Tox (PFT) strategy) during the time a lead clone is being selected for clinical material production, the toxicology studies can be accelerated significantly (approximately 4 months at Genentech), leading to a potential acceleration of 4 months for the IND submission. We explored the feasibility of the PFT strategy with three antibodies—mAb1, mAb2, and mAb3—at the 2 L scale. For each antibody, two lead cell lines were identified that generated material with similar product quality to the material generated from the associated pool. For two antibody molecules, mAb1 and mAb2, the material generated by the lead cell lines from 2 L bioreactors was tested in an accelerated stability study and was shown to have stability comparable to the material generated by the associated pool. Additionally, we used this approach for two antibody molecules, mAb4 and mAb5, at Tox and GMP production. The materials from the Tox batch at 400 L scale and three GMP batches at 2000 L scale have comparable product quality attributes for both molecules. Our results demonstrate the feasibility of using a pool of clonally derived cell lines to generate material of similar product quality and stability for use in IND‐enabling toxicology studies as was derived from the final production clone, which enabled significant acceleration of timelines into clinical development. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:1449–1455, 2017